2022
DOI: 10.3389/fmats.2022.1002195
|View full text |Cite
|
Sign up to set email alerts
|

Role of cross-diagonal reinforcements in lieu of seismic confining stirrups in the performance enhancement of square RC columns carrying axial load subjected to close-range explosive loading

Abstract: Exposure of building infrastructures to accidental or intentional blasts is an extreme load condition that may cause irreparable damage leading to the collapse of buildings. Columns being principal elements are the most important for the stability and safety of the buildings under accidental explosions and subversive blast events and therefore attract the attention of structural engineers and researchers. Some recent examples are the Beirut seaport explosion (August 2020), the explosion at an ammunition wareho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In Refs. (Sadraie et al, 2019;, Shariq et al, 2022a;Tahzeeb et al, 2022a;Tahzeeb et al, 2022b;Tahzeeb et al, 2022c;Ul Ain et al, 2021;Ul Ain et al, 2022;Anas et al, 2022i;Anas et al, 2022j;Ahmadi et al, 2022;Shariq et al, 2022b;Shariq et al, 2022c;Shariq et al, 2022d;Anas et al, 2022k;Anas and Alam, 2022d;Anas et al, 2022m;Anas et al, 2022n;Shariq et al, 2022e;Anas et al, 2022o;Anas et al, 2022p;Shariq et al, 2022f;Anas and Alam, 2022e;Shariq et al, 2022g;Anas et al, 2022q;Shariq et al, 2022h;Anas et al, 2022r) employ the Concrete Damage Plasticity (CDP) model, which takes the strain-rate effect into account. A damage plasticity model can be used to describe the mechanical behavior of concrete.…”
Section: Problem Statement and Methodology Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. (Sadraie et al, 2019;, Shariq et al, 2022a;Tahzeeb et al, 2022a;Tahzeeb et al, 2022b;Tahzeeb et al, 2022c;Ul Ain et al, 2021;Ul Ain et al, 2022;Anas et al, 2022i;Anas et al, 2022j;Ahmadi et al, 2022;Shariq et al, 2022b;Shariq et al, 2022c;Shariq et al, 2022d;Anas et al, 2022k;Anas and Alam, 2022d;Anas et al, 2022m;Anas et al, 2022n;Shariq et al, 2022e;Anas et al, 2022o;Anas et al, 2022p;Shariq et al, 2022f;Anas and Alam, 2022e;Shariq et al, 2022g;Anas et al, 2022q;Shariq et al, 2022h;Anas et al, 2022r) employ the Concrete Damage Plasticity (CDP) model, which takes the strain-rate effect into account. A damage plasticity model can be used to describe the mechanical behavior of concrete.…”
Section: Problem Statement and Methodology Usedmentioning
confidence: 99%
“…There is a thorough explanation of the CDP in Ref. (Yılmaz et al, 2018;Anas et al, 2022a;Anas et al, 2022b;Anas et al, 2022d;Ahmadi et al, 2021;Anas et al, 2020a;Anas et al, 2020b;Anas et al, 2020c;Anas and Ansari, 2021;Anas et al, 2021a;Anas et al, 2021b;Anas et al, 2021c;Anas et al, 2021d;Anas et al, 2021e;Anas et al, 2021f;Anas and Alam, 2022b;Anas and Alam, 2022c;Anas et al, 2022e;Anas et al, 2022f;Anas et al, 2022g;Anas et al, 2022h;Anas et al, 2021g;, Frontiers in Materials frontiersin.org 2022a; Tahzeeb et al, 2022a;Tahzeeb et al, 2022b;Tahzeeb et al, 2022c;Ul Ain et al, 2021;Ul Ain et al, 1007). The analysis makes use of previous research information on NSC, UHPC, and SFR-UHPC concrete found in References (Anas et al, 2022a;Anas et al, 2022b;Anas et al, 2022d).…”
Section: Problem Statement and Methodology Usedmentioning
confidence: 99%
“…To address the strain-rate effect in steel material, the present study utilizes the Johnson-Cook (J-C) approach in ABAQUS. For in-depth information on this model, refer to the works of [6][7][8][9].…”
Section:  Strain Rate Effectmentioning
confidence: 99%
“…The paramount objective is to guarantee the protection of these structures by meticulously designing them with adequate fortitude and flexibility to endure the expected level of threat in accordance with designated criteria [4][5][6][7]. Columns play a crucial role in the construction industry [8][9][10][11][12]. If any of these elements were to malfunction on a localized level, it could result in the complete failure of the entire framework, especially if the construction does not have redundant load pathways [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fibres are being used as discrete three-dimensional reinforcement to address the limitations of ordinary cement concrete and as a replacement for ultra-high-performance concrete (Bajaber and Hakeem, 2021). Fibre-reinforced concrete incorporates fibre into its mix to improve load resistance (Anas et al, 2022a;Anas et al, 2022b). Various types of fibre-reinforced concrete have been created, each with distinct and important advantages because of its various advantages, including good ductility, tensile strength, and fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%